Distribution of Ground Temperature in the Geothermal Manifestation Area of Lompio, Donggala Regency, Central Sulawesi Province - Sitti Rugayya; Badaruddin Badaruddin; Asrafil Asrafil (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
The distribution of non-volcanic geothermal energy is widely found on the island of Sulawesi, one of which is in Lompio Village, Sirenja District, Donggala Regency, Central Sulawesi Province. It is important to study the geothermal potential in the village in order to learn how the geothermal system works. This study aims to identify the distribution pattern of temperature distribution in shallow soil depths as a manifestation of the geothermal system below the surface and its relation to geothermal manifestations that appear on the surface. This research was carried out through a series of field observations and direct soil temperature measurements in the study area using a thermometer. The results show that the distribution pattern of land temperature distribution in the high-temperature zone is associated with the presence of geothermal manifestation points on the surface (hot springs). The association of temperature and manifestation is possible because the presence of hot springs is an indication of a weak zone for the release of hydrothermal fluid from the geothermal system, which is correlated with the geological structure in the research area.